PENGUATAN KELEMBAGAAN KAMPUNG IKLIM TOBEKGODANG KOTA PEKANBARU TERHADAP KEBIJAKAN PERUBAHAN IKLIM - Z, Afni; Sari, Fara Merian; Prihati, Prihati (Universitas Muhammadiyah Mataram, 2021)
Abstrak: Tujuan pengabdian masyarakat ini untuk menguatkan kelembagaan kampung iklim Kelurahan Tobekgodang, dan membuka akses dukungan kebijakan proklim dari pemerintah. Metode kegiatan dengan sosialisasi secara luring dan daring, pendampingan administratif, dan pelatihan bantuan Proklim. Dari hasil kegiatan pengabdian ini terjadi peningkatan eksistensi kelembagaan kampung Iklim Kelurahan Tobekgodang, peningkatan kapasitas kelembagaan Proklim setelah mendapat dukungan prasarana mitigasi dan adaptasi perubahan iklim, peningkatan kemampuan SDM serta manfaat yang dapat langsung diaplikasikan untuk membentuk masyarakat berketahanan iklim di tingkat tapak.Abstract: Efforts to mitigate and adapt to climate change in Indonesia are still constrained by the climate village institutional program (Proklim) at the site level. The purpose of this community service is to strengthen the climate village institution of Tobekgodang Village, and to open access to pro-climate policy support from the government. Methods of offline and dare socialization activities, administrative assistance, and training for Proklim assistance. From the results of this service activity, there was an increase in the existence of the Climate Village institution, Tobekgodang Village, the increase in the institutional capacity of Proklim after receiving the support of climate change mitigation and adaptation infrastructure, increasing the capacity of human resources and benefits that can be directly applied to form a climate-resilient community at the site.